A Global Analysis of Future Water Deficit Based On Different Allocation Mechanisms. Issue 8 (28th August 2018) - Bijl, David L.; Biemans, Hester; Bogaart, Patrick W.; Dekker, Stefan C.; Doelman, Jonathan C.; Stehfest, Elke; van Vuuren, Detlef P.
Abstract: Freshwater scarcity is already an urgent problem in some areas but may increase significantly in the future. To assess future developments, we need to understand how future population growth, agricultural production patterns, energy use, economic development, and climate change may impact the global freshwater cycle. Integrated models provide opportunities for quantitative assessment. In this paper, we further integrate models of hydrology and economics, using the models IMAGE and LPJmL, with explicit accounting for (1) electricity, industry, and municipal and irrigation water use; (2) intersectoral water allocation rules at the 0.5° × 0.5°grid scale; and (3) withdrawal, consumption, and return flows. With the integration between hydrology and economy we are able to understand competition dynamics between the different freshwater users at the basin and grid scale. We run model projections for three Shared Socioeconomic Pathways (SSPs), more efficient water use, and no expansion of irrigated areas to understand the competition dynamics of these different allocation mechanisms. We conclude that (1) global water withdrawal is projected to increase by 12% in SSP‐1, 26% in SSP‐2, and 29% in SSP‐3 during 2010–2050; (2) water deficits (demand minus allocated water) for nonagricultural uses are small in 2010 but become significant around 2050; (3) interannual variability of precipitation results in variability of water deficits; (4) water use efficiency improvements reduce water withdrawal but have little impact on water deficits; and (5) priority rules at the local level have a large effect on water deficits, whereas limiting the expansion of irrigation has virtually no effect. Key Points: We study future competition between irrigation and other water uses with a detailed integrated model of economic and hydrological processes We find that even substantial water use efficiency improvements have little impact on water deficits (demand minus allocated water volume) Local allocation rules have a large effect on water deficits, whereas a basin‐level strategy of limiting irrigation has less effect